2014
DOI: 10.3122/jabfm.2014.03.130264
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Implementation and Outcomes of Health Behavior and Mental Health Assessment

Abstract: Background Assessing patient-reported health behaviors is a critical first step to prioritizing prevention in primary care. We assessed the feasibility of point-of-care behavioral health assessment in nine diverse primary care practices, including four federally-qualified health centers (FQHCs), four Practice-based Research Network (PBRN) practices, and a Department of Veterans Affairs (VA) practice. Methods In this prospective mixed-methods study, practices were asked to integrate a standardized paper-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Generally, our concordance findings were consistent with studies that have used similar methods ( 7 , 25 , 26 ). Our level of agreement was similar to previous research assessing data quality between ambulatory medical record data and patient survey data for diabetes and BMI, but we had a higher level of concordance for HBP, HBP medication, and hyperlipidemia and a lower level of concordance for lipid-lowering medication ( 26 ).…”
Section: Discussionsupporting
confidence: 92%
“…Generally, our concordance findings were consistent with studies that have used similar methods ( 7 , 25 , 26 ). Our level of agreement was similar to previous research assessing data quality between ambulatory medical record data and patient survey data for diabetes and BMI, but we had a higher level of concordance for HBP, HBP medication, and hyperlipidemia and a lower level of concordance for lipid-lowering medication ( 26 ).…”
Section: Discussionsupporting
confidence: 92%
“…Study methods and pilot data have been reported previously. 16,17 The study was approved by the Virginia Commonwealth University (VCU) (#HM12746), (#12-0017900), and 5 other participating institutional review boards. …”
mentioning
confidence: 99%
“…However, the use of valid and reliable assessment tools to collect self-reported data on smoking, drinking, and exercise behaviors in primary care settings remains challenging. [36][37][38] The majority of referrals were self-referrals, friends and family, and medical in origin. The determinants of self-referrals to chiropractic physicians include patient attitudes, better health status, and affordable costs.…”
Section: Discussionmentioning
confidence: 99%